Audit of the Service Information System in the Profaskes Application at the Khoirunnisa Ciruas Clinic Using the Cobit 5.0 Framework - Aisah, Anggi Nur; Auliana, Sigit; Permana, Basuki Rakhim Setya; Aryono, Gagah Dwiki Putra; Mansyuri, Umar (Indonesian Research Journal on Education, 2024)
Information system audits are carried out to determine the extent to which information system management in an organization, institution or company complies with established procedures and standards. This research aims to determine the level of capability in using the service information system in the Profaskes application at the Khoirunnisa Ciruas Clinic. The methods used in this research include data collection through interviews, observation and document analysis. This research also uses the COBIT 5.0 framework. The research process begins with problem identification, data collection, initiation, assessment planning, direction, data collection, data validation, process attribute ranking, and reporting results. The aim of this research is to determine the level of capability and provide recommendations to clinics using the COBIT 5.0 process assessment model, which consists of the initiation, assessment planning, data collection, data validation, process attribute levels, and results reporting stages. Then, after the analysis process, the results of the service information system audit on the Profaskes application using the COBIT 5.0 framework, with a focus on the DSS02 domain (managing service requests and incidents) and the DSS05 domain (managing security services), show that the current level of capability is at the level 2. From this research, it can be concluded that the condition of the service information system at the Khoirunnisa Clinic is good but needs further improvement.